Innovative Construction Technique Using Ferrocrete - Sagar Lalage5, Sujit Matale1 , Shruti Krishnakumar2 , Atul Yadav3 , Aashika Patidar4 , (International Journal of Scientific Research and Management (IJSRM), 2016)
In recent years, speedy construction is necessary for overall development to satisfy the needs of current population.There is huge mismatch between the infrastructural needs and its development. This study aims to increase the pace ofconstruction using precast ferrocrete mould which would eradicate the use of formwork completely. Significant amount of workhas been carried out on confinement of column with ferrocrete laminates for strengthening and jacketing purposes. Use offerrocrete mould as an external confinement to concrete specimen has been thoroughly studied and investigated in thisexperimental study. The experimental investigation included casting of six M20 blocks in two batches each having differentspecifications. All the specimens were tested for direct un-axial compression. The change in stress carrying capacity of confinedspecimens was compared with that of unconfined specimens having similar size and dimensions. After comparison, the increasein load carrying capacity observed in ferrocrete confined specimens was 71.18%, as compared to the strength of unconfinedspecimens.